A systematic review of the neurobiological aspects of memory in the aging process - Eduardo Moreira de Oliveira; Priscilla Tiemi Kissaki; Tiago Nascimento Ordonez; Thaís Bento Lima-Silva (Dementia & Neuropsychologia)
Abstract A systematic review of the neuroanatomical literature was performed to determine the neuropharmacological aspects most relevant to the study of memory processes. Articles were retrieved using the search terms "biology of memory", "memory and aging", "memory impairment", "elderly and memory," and their equivalents in Portuguese. Of the studies surveyed, five studies dealt with epidemiological and demographic issues, 12 were clinical trials i.e. were based on testing and implementation of instruments in human subjects, 33 studies were basic research involving studies of mice, rats and non-human primates, and biochemical and in vitro trials and finally, 52 studies were literature reviews or book chapters which in our view, fell into this category. Conclusions: The work sought to highlight which neural networks are most involved in processing information, as well as their location within brain regions and the way in which neurotransmitters interact with each other for the formation of these memories. Moreover, it was shown how memory changes during the normal human aging process, both positively and negatively, by analyzing the morphological alterations that occur in the brain of aging individuals.